2011
DOI: 10.4061/2011/727313
|View full text |Cite
|
Sign up to set email alerts
|

Virulence Plasmid (pYV)-Associated Expression of Phenotypic Virulent Determinants in PathogenicYersiniaSpecies: A Convenient Method for Monitoring the Presence of pYV under Culture Conditions and Its Application for Isolation/Detection ofYersinia pestisin Food

Abstract: In Yersinia pestis, Y. pseudotuberculosis, and Y. enterocolitica, phenotypic expression of virulence plasmid (pYV: 70-kb)-associated genetic determinants may include low-calcium response (Lcr, pinpoint colony, size = 0.36 mm), colony morphology (size = 1.13 mm), crystal violet (CV) binding (dark-violet colony), Congo Red (CR) uptake (red pinpoint colony, size = 0.36 mm), autoagglutination (AA = cells agglutinate), and hydrophobicity (HP = clumping of cells). Y. pseudotuberculosis is chromosomally closely relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…In addition, the growth of these isolates on CR-MOX at 37°C indicated that they did not contain pYV. It cannot be ruled out that the four pYV-negative isolates lost their virulence plasmid during cultivation in the laboratory, because pYV is known to be a rather unstable plasmid (41,42). Strains devoid of pYV are considered to be nonpathogenic, even though pYV-negative Y. pseudotuberculosis strains have been isolated from patients (1,43).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the growth of these isolates on CR-MOX at 37°C indicated that they did not contain pYV. It cannot be ruled out that the four pYV-negative isolates lost their virulence plasmid during cultivation in the laboratory, because pYV is known to be a rather unstable plasmid (41,42). Strains devoid of pYV are considered to be nonpathogenic, even though pYV-negative Y. pseudotuberculosis strains have been isolated from patients (1,43).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, other environmental stresses such as temperature, atmosphere, culture conditions, freezing, salt, and acidic pH have not been shown to induce pYV loss, and Y . enterocolitica retain the pYV and are still capable of causing food poisoning (Bhaduri , , , , ; Bhaduri and others , , ; Bhaduri and Phillips ; Bhaduri and Smith , ; Bhaduri and Sommers ). Figure shows the percentage of colonies which failed to bind CV in the presence of air, or combinations of CO 2 or N 2 .…”
Section: Resultsmentioning
confidence: 99%
“…. culture conditions, freezing, salt, acidic pH, and calcium concentration can affect virulence-plasmid associated phenotypes of Y. enterocolitica, Y. pseudotuberculosis, and Y. pestis such as Lcr, colony size, CV binding, CR-uptake, AA, and HP (Bhaduri and others 1988(Bhaduri and others , 1993(Bhaduri and others , 2011Bhaduri 1995Bhaduri , 2005Bhaduri , 2006Bhaduri , 2011Bhaduri , 2014Bhaduri and Sommers 2008;Bhaduri and Phillips 2011;Bhaduri and Smith 2012). Y. enterocolitica displays pYV-dependent formation of microcolonies in collagen gels, a system to mimic infection in living tissue when incubated at 37°C.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the isolate lacks pYV. Indeed, it should be consider that this unstable plasmid can be easily lost during cultivation in the laboratory (Bhaduri and Smith, 2011 ) and pYV-negative Y. pseudotuberculosis strains have been isolated from infected human patients (Fukushima, Sato, and Nagasako, and Takeda 1991 ). For instance, in Galindo and collaborators ( 2011 ) pYV was absent in one – fourth of the known virulent serotypes, which harbored HPI and/or YPMa.…”
Section: Discussionmentioning
confidence: 99%